Financial Reporting Enforcement: Impact and Consequences - Carsten Allerslev Olsen (Copenhagen Business School (CBS), 2018)
This dissertation explores how financial reporting enforcement differs in Europe and how these differences influence the materiality assessment and disclosure decisions made by the preparers of the financial statement. Furthermore, it analyses how financial reporting enforcement influences the auditors' auditing efforts, which are made in conjunction with the impact of the enforcement of auditors and limitations on the auditors' liability. However, research indicates that strict enforcement is a prerequisite for ensuring compliance with accounting regulations (Hail and Leuz 2006, Daske et al. 2008, 2013, Ernstberger et al. 2012, Christensen et al. 2013, Leuz and Wysocki 2016). Nevertheless, enforcement remains at the discretion of the individual member states, which has led to heterogeneous enforcement despite recent attempts to strengthen and harmonise it (Hirtz et al. 2012, Christensen et al. 2013, Brown et al. 2014). This heterogeneous enforcement has created a particular need to understand how enforcement influences financial reporting if the primary users must be able to use it as a reliable source of information. This issue is investigated in the following three papers that compose this dissertation.
hdl:10398/9613
Keywords: 650